Fe/SBA-15: Characterization and its application to a heterogeneous solar photo-Fenton process in order to decolorize and mineralize an azo dye - Arroyo Gómez, José Joaquín (2020)
Fe/SBA-15 catalyst with different iron (Fe) loads (6% and 10% wt.) was synthesized via incipient wetness impregnation. The potential photocatalytic properties were tested using solar radiation, as a novel catalyst in heterogeneous Fenton approach to degrade Methyl Orange azo dye. A partial pore blocking of the substrate by Fe nanoparticles was detected and the main form of Fe present was Fe2O3. When the Fe(10%)/SBA-15 catalyst was used for heterogeneous solar photo-Fenton reaction, total discoloration of the effluent was achieved in 90 min, and 89% of COD was removed in 240 min. Short-chain linear carboxylic acids were followed over time, as well as inorganic ions.